Cultural Differences in Humor Perception, Usage, and Implications - Jiang, Tonglin; Li, Hao; Hou, Yubo (Frontiers in Psychology, 2019)
Humor is a universal phenomenon but is also culturally tinted. In this article, we reviewed the existing research that investigates how culture impacts individuals’ humor perception and usage as well as humor’s implications for psychological well-being. Previous research has substantiated evidence that Easterners do not hold as positive an attitude toward humor as their Western counterparts do. This perception makes Easterners less likely to use humor as a coping strategy in comparison with Westerners. Despite this difference, Westerners and Easterners have similar patterns in the relationship between their humor and psychological well-being index, though the strength of the relationship varies across cultures. Implications and potential future research avenues discussed.